Motivational characteristics in mathematical achievement: A study of gifted high-achieving, gifted underachieving and non-gifted pupils - Vlahović-Štetić, Vesna (Array, 1999)
The aim of this study was to examine whether motivational-emotional variables such as intrinsic orientation toward schoolwork, mathematics anxiety, academic self-esteem, attribution of success and failure in mathematics, and situational interest in mathematics could differentiate different groups of mathematically gifted pupils. The research was based, theoretically, on an interactional model of giftedness. The sample consisted of 147 selected primary school pupils (boys and girls 9-10 yrs of age) who were assigned to the following groups for comparison: 31 mathematically gifted achievers, 31 mathematically gifted underachievers, and 85 mathematically non-gifted pupils. The results of a discriminant analysis show that the gifted pupils differ from the non-gifted ones in attaining higher levels of intrinsic orientation toward mathematics, lower mathematics anxiety, lower attribution of success to external factors and effort, and lower attribution of failure to external factors and abilities. Also, gifted achievers have lower attribution of success to effort than gifted underachievers and non-gifted pupils.